PROFIT EQUALIZATION RESERVE (PER) AS AN EFFORT TO MITIGATE THE RISK OF RETURNS IN SHARI'A BANKING IN THE PERSPECTIVE OF THE RULES Ø§Ù„Ù’Ù…ÙŽØ´ÙŽÙ‚ÙŽÙ‘Ø©Ù ØªÙŽØ¬Ù’Ù„ÙØ¨Ù Ø§Ù„ØªÙŽÙ‘ÙŠÙ’Ø³ÙÙŠÙ’Ø±Ù - Muhamad Hamam Nasiruddin; Luthfiana Basyirah; Miftachus Surur (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
The application of Profit Equalization as an effort to mitigate the risk of returns on Islamic financial institutions, especially Islamic banking is still being a question for practitioners and academics, some groups support and some groups criticize, so this research aims to examine the application of the Profit Equalization Reserve (PER) as an effort to mitigate the risk of returns in Islamic banking perspective of third main principle,Â  namely Ø§Ù„Ù’Ù…ÙŽØ´ÙŽÙ‚ÙŽÙ‘Ø©Ù ØªÙŽØ¬Ù’Ù„ÙØ¨Ù Ø§Ù„ØªÙŽÙ‘ÙŠÙ’Ø³ÙÙŠÙ’Ø±Ù, Method in this study is a qualitative method with secondary data processing taken from literatures which related to PER management. This research shows that the risk of returns is masyaqqoh al 'azimmah, which is a serious difficulty and can affect the continuity of the Islamic banks activities. So, rukhshoh is needed which in this problem is the application of income smoothing without mitigation or with mitigation (PER), PER in this case is Takhfif Taqdim which is, risk mitigation efforts before they arise. The result of this research is that PER application is permissible and legitimate as long as it does not violate the Shari'a and Islamic economic principles, meaning that all of reports and information must be conveyed clearly to customers so as to avoid gharar elements.